The emergence of city food networks: Rescaling the impact of urban food policies. (August 2021) - Moragues-Faus, Ana
Highlights: First comparative analysis of international and national city food networks. Translocal governance analysis shows fluid policy processes and interactions. Cross-scalar food policy alignment is key rather than coordination. The metagovernance of networks reveals lower state involvement in scaling-up efforts. New questions arise around processes of alignment/decision-making and justice outcomes. Abstract: Hundreds of cities across the globe are mobilising the convening power of food to deliver food security and sustainability outcomes supported by an increasing number of national and international city food networks devoted to scale-up and out this urban food revolution. This paper presents the first comparative analysis of this increasingly networked urban foodscape based on data from 13 national and international initiatives which together represent more than 500 cities across the globe. By applying a translocal governance framework, the paper explores the different aims, structures and mechanisms activated by this complex landscape of networks and how these intrinsic characteristics endow them with diverse strengths and limitations. To examine further the role of networks in rescaling the impact urban food policies, I analyse the metagovernance of these initiatives exploring discourses around coordination of these networks and identifying potential convergence points. Results from this study are translated into policy recommendations aimed at unfolding further the transformative capacity of translocal networks and elevate their role in unfolding a more integrated and equitable new urban food agenda; mainly by proposing to reinforce the cross-scalar alignment of food policies, making the case to invest in connective infrastructure such as network and backbone organisations, work with a wider diversity of agents, and provide open spaces that democratise access to collective knowledge and capacities. c. As urban food policies become the new norm, this research stresses the need for rescaling food system interventions that effectively deliver social and spatial justice in an increasingly polarised word.